Anti–Vascular Endothelial Growth Factor Therapy for Diabetic Retinopathy: Consequences of Inadvertent Treatment Interruptions - Wubben, Thomas J.; Johnson, Mark W.; Sohn, Elliott H.; Peairs, James J.; Kay, Christine N.; Kim, Stephen J.; Gardner, Thomas W.; Paulus, Yannis M.; Zacks, David N.; Steinle, Nathan C.; Avery, Robert L.; Berrocal, Maria H. (American journal of ophthalmology, 2019)
To illustrate that patients with diabetic retinopathy who are treated exclusively with anti–vascular endothelial growth factor (VEGF) therapy and have an interruption in treatment may experience marked progression of disease with potentially devastating visual consequences. Retrospective, multicenter, case series. Retrospective review of patients treated exclusively with anti-VEGF therapy for proliferative diabetic retinopathy (PDR) or nonproliferative diabetic retinopathy (NPDR), with or without diabetic macular edema (DME), and temporarily lost to follow-up. Baseline disease characteristics, cause and duration of the treatment interruption, and resulting disease progression, complications, and outcomes were assessed. Thirteen eyes of 12 patients with type 2 diabetes were identified. The mean age was 57 ± 10 years, and 50% were women. Anti-VEGF therapy was indicated for PDR with DME in 7 (54%) eyes, PDR without DME in 3 (23%) eyes, and moderate to severe NPDR with DME in 3 (23%) eyes. Eight eyes had visual acuity (VA) of 20/80 or better before treatment interruption. The median duration of treatment hiatus was 12 months. Reasons for treatment interruption included intercurrent illness (31%), noncompliance (31%), and financial issues (15%). Complications upon follow-up included vitreous hemorrhage (9 eyes), neovascular glaucoma (5 eyes), and traction retinal detachment (4 eyes). Despite treatment of these complications, 77% of eyes lost ≥3 lines of VA, with 46% of eyes having a final VA of hand motion or worse. Diabetic patients are subject to significant lapses in follow-up because of illness, financial hardship, or noncompliance. In patients with diabetic retinopathy, especially PDR, who are managed with anti-VEGF therapy alone, unintentional treatment interruptions can result in irreversible blindness.